2006
DOI: 10.1016/j.ejcts.2006.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Survival in elderly patients with severe aortic stenosis is dramatically improved by aortic valve replacement: results from a cohort of 277 patients aged ≥80 years☆

Abstract: Prognosis of medically managed severe calcific AS in the elderly patients is dismal. AVR appears to improve survival of these patients and should be strongly considered in the absence of other major comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
1
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(122 citation statements)
references
References 16 publications
4
105
1
11
Order By: Relevance
“…Still, 41% of these patients with severe symptomatic AVS were treated medically. A similar survival pattern was observed in the study by Varadarajan and coworkers (Varadarajan et al, 2006). In their hands, surgically treated patients showed improved 1-year, 2-year and 5-year survival rates of 87, 78 and 68%, respectively, as compared with 52, 40 and 22%, respectively, in those managed medically.…”
Section: Natural History Of Aortic Stenosis and Conventional Treatmentsupporting
confidence: 67%
“…Still, 41% of these patients with severe symptomatic AVS were treated medically. A similar survival pattern was observed in the study by Varadarajan and coworkers (Varadarajan et al, 2006). In their hands, surgically treated patients showed improved 1-year, 2-year and 5-year survival rates of 87, 78 and 68%, respectively, as compared with 52, 40 and 22%, respectively, in those managed medically.…”
Section: Natural History Of Aortic Stenosis and Conventional Treatmentsupporting
confidence: 67%
“…Although aortic stenosis (AS) is robustly associated with adverse outcomes,2, 3 aortic sclerosis has also been associated with an increased risk of cardiovascular morbidity and mortality,4 and aortic sclerosis is a significant risk factor for progression to AS 5. More important, AV calcification and stenosis are associated with similar risk factors as atherosclerosis,1, 6, 7 and a wealth of data now point towards parallel active processes leading to AV dysfunction, including inflammation, lipid deposition, and calcification 8…”
Section: Introductionmentioning
confidence: 99%
“…Elective FS-AVR performed through FS has been deemed a safe procedure since it carries low morbidity and short/long-term mortality rates. Specifically, multiple studies found AVR to be associated with favorable long-term survivorship, with average times ranging between 6.2 and 11.2 years postsurgery depending on age [42,47]. As such, AVR (isolated or concomitant with coronary Table 2.…”
Section: Discussionmentioning
confidence: 99%